A Convergent Total Synthesis of the Telomerase Inhibitor (±)‐γ‐Rubromycin1. Issue 17 (12th March 2014) - Wilsdorf, Michael; Reissig, Hans‐Ulrich
Abstract The total synthesis of the human telomerase inhibitor γ‐rubromycin in its racemic form was accomplished in 3.8 % overall yield. The key feature of this synthesis is an efficient acid‐catalyzed spiroketalization for the construction of the spiroketal core. The required electronically well‐balanced spiroketal precursor was obtained by the convergent assembly of a naphthyl‐substituted aldehyde, an α‐methoxyallyl‐γ‐silyl‐substituted phosphonate as the central C3 building block, and a highly functionalized aryl Grignard reagent. Another key feature is the late‐stage construction of the isocoumarin moiety and a simultaneous protodesilylation furnishing the known methyl aryl ether protected precursor of γ‐rubromycin.